Rizaldi Patria Efisiensi Anggaran Biaya Pada Pembangunan Masjid Haya Bohol, Rongkop, Gunungkidul - Patria, Rizaldi; Eko Bawono, Septiono; Putri Rahayu, Anggita (Universitas Veteran Bangun Nusantara, 2024)
The construction of Masjid Haya was carried out to complement public facilities in Kalurahan Bohol, Rongkop, Gunungkidul. The construction was carried out through mutual cooperation. In the context of public buildings, collaboration and community cooperation become determining factors for the success of the project. Community participation and effective management are two mutually supportive factors in the effort to build high-quality and sustainable public facilities. This research aims to determine the efficiency of the budget for public facility construction in the implementation of development with community participation. The method used is quantitative analysis and field interviews to determine category grouping. Interviews were conducted to delve into information regarding the cost needs for development and community involvement. The results of the calculation analysis show: first, the percentage of the budgetary needs for materials/raw materials if the work involves a jointly owned building from the two groups is 3,35%; second, the percentage of the budgetary needs for third parties is 34,173% of the total; third, the percentage of the budget carried out through mutual cooperation from the overall budget is 8,341%. Work that does not require skill can be carried out through mutual cooperation if the work involves a jointly owned building, as it can reduce the budget cost by 10.564%. This third party consists of workers who have expertise in their respective fields and are capable of carrying out the work well and efficiently. The analysis results show that the labor cost ranges from 30% to 40%, depending on the difficulty of the work in the field. The percentage of the material budget contributed by the local community for the construction is 3,35%.